Genome-wide analysis of AP2/ERF transcription Factors in Cymbidium sinense reveals their impact on orchid diversity - Wei, Yong-Lu; Jin, Jian-Peng; Li, Jie; Xie, Qi; Lu, Chu-Qiao; Gao, Jie; Zhu, Gen-Fa; Yang, Feng-Xi (Frontiers in Plant Science, 2025)
Cymbidium sinense is a significant traditional Chinese horticultural crop, valued both economically and ornamentally. The APETALA2/ethylene response factor (AP2/ERF) transcription factors play crucial roles in regulating growth, development, cell differentiation, and responses to both biotic and abiotic stresses in plants. However, the regulatory functions of AP2/ERF factors in C. sinense remain poorly understood. In the present study, 116 AP2/ERF genes were first identified from C.sinense genome. Based phylogenetic analysis, these genes were categorized into five groups: AP2, RAV, ERF, DREB, and Soloist. Within the ERF group, two subtypes were identified: ERF (containing six subtypes from ERF B1 to ERF B6) and DREB (containing six subtypes from DREB A1 to DREB A6), consistent with the classification in Arabidopsis. Significant variation was observed in gene exon-intron structures, though motifs and domain structures were highly conserved. Duplication events and collinearity analyses across five species were also conducted. Further investigations into potential cis-elements in promoter regions and expression profiles of 44 different samples, along with the analysis of 11,197 CsAP2/ERF target genes (functional annotation of 9,566), revealed diverse transcriptional regulatory patterns. GO enrichment and KEGG pathway analysis further elucidated these patterns. To validate transcriptome-based predictions, qRT-PCR analysis was performed on ten key CsAP2/ERF genes, showing high consistency with RNA-seq data. Moreover, a yeast one-hybrid (Y1H) assay confirmed that CsAP2_51 directly binds to the promoter of CsAG, a key gene involved in gynostemium development, providing experimental evidence for the regulatory role of CsAP2/ERF in floral morphogenesis. A regulatory model was proposed to illustrate the potential roles of CsAP2/ERF genes in floral patterning and flower color variation. Our findings deepen the understanding of CsAP2/ERF gene functions in C. sinense and provide a valuable foundation for future studies on the molecular mechanisms underlying its growth, development, and ornamental traits.